Compression and shear wave velocities of unsaturated soils - Wee, Rayner Jian De. (2009)
In this report, an ultrasonic velocity test system consisting of compression and shear wave transducers, a pulser and a data acquisition system was used to obtain the compression and shear wave velocities of three different soil types. The pressure plate test was also conducted to determine the change in water content over various matric suction values. The effects of degree of saturation, the compression and shear wave velocities were investigated. Gassmann equation was found to be inadequate in estimating the P-wave velocity. A modification to Gassmann equation still underestimates the P-wave velocity by 22% to 63%.